Proceedings of the Seminar on Research Findings 2008 (IIUM Press, 2009)
The proceedings, among others, undertook the compilation of the fifty-two research projects completed in 2007 by academicians from IIUM, coming from all of its twelve kulliyahs. This is no doubt a commendable effort on their part, and reflects the fulfillment of their communal duty (fard kifayah) to the Ummah. this work forms an integral part of IIUM's well-propagated philosophies of Islamization, Integration, Internationalization and Comprehensive Excellence.